Rashba Spin Orbit Interaction Effect on Spin Current in a Quantum Wire with Magnetic Field - Kumar, Manoj; Lahon, Siddhartha; Mohan, Man (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
We study the spin current in a quantum wire subjected to magnetic fields in the presence of Rashba spin orbit interaction. For an infinite superlattice wire, we find that the spin current density is strongly affected by the nature of the sub bands. The results are presented as a function of transverse coordinate, magnetic field and Rashba spin orbit interaction strength. Our results indicate an increase of spin current density with the increase of Rashba factor. The roles of confinement strength and magnetic fields as control parameters on the spin current have been demonstrated.